The effect of ozone gel as adjunct treatment in patients of periodontitis according to bleeding on probing and platelet-activating factor (A split-mouth randomized controlled clinical trial) (Mustansiria Dental Journal, 2023)
Materials and methods: total sample composed of 58 periodontal pockets was divided into two groups. The control group had 28 periodontal pockets treated with scaling and root planning only, while the test group had 30 periodontal pockets treated with scaling and root planning and ozone gel. Two applications of the gel were applied at baseline and one month after the treatment .platelet activating factor (biomarker) and clinical parameters of bleeding on probing are measured at baseline, after one month, and after three months. In the second visit of periodontal therapy (after one day), GCF samples were obtained from patients by gently inserting periocol paper into the selected depth of the pocket when resistance was encountered. The periocol paper was then left in position for 30 seconds before being removed and weighed on a chemical balance. Each paper strip was placed in a tube keeping o.3ml of buffer phosphate saline, then transferred and stored at -40C. Calculated the difference between the weight of periocol paper before and after exudate absorption of gingival crevicular fluid. After sample storage for five minutes, the samples were centrifuged at 13,000 rpm.Results: Test sites showed a greater reduction in bleeding on probing and there was a significant difference in the first month only when compared to control sites (Fisher exact=0.010) but no significant difference at three months. The platelet-activating factor was reduced significantly by ozone gel in the first month with only a p-value (0.000) but no significance at one and three months.Conclusion: In comparison to SRP alone, treatment with ozone gel as an adjuvant therapy yields no statistically significant improvement after three months.